Cerebral Arteriovenous Malformations: Diagnostic Value of Echo-Enhanced Transcranial Doppler Sonography Compared with Angiography - Uggowitzer, Martin M.; Kugler, Christian; Riccabona, Michael; Klein, Günther E.; Leber, Klaus; Simbrunner, Josef; Quehenberger, Franz (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The purpose of our study was to examine the clinical value of echo-enhanced transcranial power Doppler sonography (EE-TCD), including it ability to assess hemodynamic parameters of the intracranial vasculature, in patients with suspected cerebral arteriovenous malformations (AVMs) and to compare this method with angiography.METHODS: Sixteen patients with suspected cerebral AVMs were examined with EE-TCD and angiography. As an echo-enhancing agent, SHU 508A (Levovist) was administered intravenously by bolus injection in nine patients and by continuous infusion in seven. Sonograms were reviewed without knowledge of other imaging results and were correlated with angiographic findings.RESULTS: Angiography showed AVMs in 12 of 16 patients. Eleven lesions were located in the anterior or middle fossa and one was in the posterior fossa. EE-TCD was slightly less sensitive in the detection of AVMs (92%, 11/12 lesions), since in one patient the lacking acoustic window did not allow a transcranial examination. EE-TCD slightly underestimated AVM size compared with angiographic findings but showed feeding arteries with sufficient acoustic properties. In seven patients (58%), angiography revealed a coincidental blood supply from another intracranial or extracranial vessel, which was missed by EE-TCD in all cases. Assessment of peak systolic velocities and resistive indexes resulted in a higher (mean, 191.1 cm/s) and a lower (mean, 45.7%) value, respectively, in the feeding arteries as compared with the contralateral arteries (mean, 101.8 cm/s and 55.6%, respectively). Side-to-side differences were significantly higher in patients with AVMs than in those without a malformation. Signal enhancement was markedly longer with continuous infusion (mean, 520 seconds ± 28.2) than with bolus injection (mean, 145 seconds ± 10.5) of the contrast agent.CONCLUSION: In our limited study group, EE-TCD was a sensitive method for the detection of AVMs, and Levovist proved to be a safe and effective echo-enhancing substance.